Cash Waqf in Islamic Economy: Conceptual Analysis, Regulation and Empowerment Potential - Azhar Jaafar; Burhanuddin Burhanuddin; Fauzi Akmal (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Waqf holds significant potential as an instrument for social and economic empowerment within the Islamic economic system. One of its evolving forms is cash waqf, which offers substantial opportunities when managed with integrity and professionalism. This study aims to examine the concept of cash waqf, including its definition, pillars, conditions, legal foundations, and utilization in religious and social contexts. The research employs a qualitative method with a literature study approach, drawing upon primary sources such as the Quran, Hadith, scholarly opinions, and state regulations governing waqf. Findings indicate that cash waqf can be productively utilized in education, religious infrastructure development, and healthcare services. Management is carried out by nazhir through transparent and accountable systems supported by Islamic financial institutions. The implications highlight the importance of optimizing cash waqf management as a means of socio-religious empowerment and strengthening the economic welfare of the Muslim community.